STUDENTS' ENGAGEMENT IN ONLINE LEARNING USING WHATSAPP GROUP DURING COVID-19 PANDEMIC - Nugroho Nugroho (Linguistics and ELT Journal, 2022)
Starting in the odd semester of 2020/2021, the University of Indraprasta PGRI will provide online or distance learning. Because of government laws on Large-Scale Social Restrictions, online learning is finished. Distance learning has always used technology to apply its knowledge, beginning with the most basic methodology and progressing to the most advanced. According to PDDIKTI 2020, the study sample is 206 of 4106 active students of the Indraprasta PGRI University with language and arts majors in English education. One of the reasons student participation on campus should be a concern is that it is a crucial factor in learning and academic success. Learning performance is measured in academic achievement, character development, and satisfaction in the classroom. The study aims to learn about students' participation in online Learning during Covid-19. The study employs a survey approach with a degree of descriptive interpretation and quantitative data analysis. The study results conclude that most English education students have very high engagement in online learning using WhatsApp application with 69% or as much as 144 students. Twenty-seven percent of the students have high, 3% have moderate, and 1% have low engagement.